Declaration of feminine individuality in Gloria Naylor’s Novels: Empowering Women through Fiction (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Gloria Naylor, a novelist with a difference is a brilliant writer and true humanist who wants to change the male- centric culture through her novels. She awakens and motivates women to feel confident and self–reliant. All the characters of her novels face hardships in their life but come out as warriors of their life because they do not lose confidence and hope to change their situation.